A New Resin Containing Aminopropylphosphonate Chelating Ligand for High‐Performance Mitigation of Heavy Metal Ions. Issue 47 (17th December 2018) - Kazi, Izzat W.; Ullah, Nisar; Ali, Shaikh A.
Abstract: Cyclopolymerization, initiated by t‐butylhydroperoxide, of an aqueous solution of N ‐(3‐phosphonopropyl)diallylammonium hydrochloride and cross‐linker tetraallylpiperazinium dichloride in 9:1 mol ratio, led to a pH‐responsive cross‐linked resin (80% yield). The resin showed exceptional efficiency for entrapping toxic metal ions from aqueous systems. Using Langmuir adsorption isotherm, the respective maximum uptake ( Q m ) of Pb 2+ and Cu 2+ ions was determined to be 7.18 and 6.76 mmol g −1 . The very impressive performance accorded the resin a prestigious place among many sorbents in recent works. The adsorption data fitted second‐order kinetics with respective E a of 35.5 and 31.1 kJ mol −1 for Pb 2+ and Cu 2+ ions. While the initial rapid adsorption of metal ions was due to film diffusion, the slower adsorption followed intraparticle diffusion. SEM and EDX analyses confirmed the metal ions' adsorption onto sorbent. The negative Δ G ° and positive Δ H ° values demonstrated the endothermic adsorption as a favorable process. The sorbent is recyclable as evinced by the excellent adsorption/desorption process. Abstract : We report here the synthesis of a novel pH‐responsive resin by cyclopolymerization protocol. The respective uptake ( Q m ) of Pb 2+ and Cu 2+ ions by the resin were determined to be 7.18 and 6.76 mmol g ‐1 . The very impressive performance accorded the resin a prestigious place among many sorbents in recent works.